Effect of organic dye on the growth and optical properties of KDP - Pritula, I.M.; Velikhov, Yu.N.; Levchenko, A.N.; Kolybayeva, M.I.; Puzikov, V.M.; Tyutyunnik, V.B.; Doroshenko, A.O. (Functional Materials, 2004)
It is established that Xylenol Orange (XO) preferentially dyes the faces {100} and {010} of KDP crystal. The dye content in the crystals is found to be practically independent of its content in the solution. It is revealed that the crystal habit changes in the presence of organic dyes: the ratio of the faces {100} and {010} (x and y) at maximum concentrations reaches 1.2. Studied is the influence of the mother solution acidity on the character of the crystal coloration. It is established that the color and dyeing intensity depend on the solution’s pH. The optical transmission spectrum of KDP with dye (solutions and crystals) is registered. The characteristic absorption peaks are observed in the region from 200 to 600 nm. Revealed is the transmission anisotropy in the directions x and y for the dyed crystals. Dichroism in KDP + XO is shown to depend on the orientation. The emission and excitation spectra of the dyed crystals are measured. The values of bulk laser damage threshold are determined. Discussed is the mechanism of the organic dye incorporation into the crystal matrix.